Community Empowerment through Village-Owned Enterprises Activities as a Regional Development Strategy in Indonesia: A Systematic Literature Review - Lestary, Riska Ayu; Hadi, Krishno (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
This study aims to determine community empowerment that can be done through the Village-Owned Enterprises (Badan Usaha Milik Desa/BUMDes) program to support village income. Problems related to disparities in villages in areas that require a development strategy through empowerment programs, require the role of government and society in carrying it out. The type of research of this article uses the literature review method which comes from previous research indexed by the Scopus Database and processed in the Vosviewer application. In this study, it is revealed that the role of BUMDes can increase village income and prosper the village community, and then it can support development in the region. The role of rural communities is very much needed for regional development efforts; especially during the COVID-19 pandemic the existence of BUMDes can increase the country's economy which had experienced a decline. The main key in increasing BUMDes as a regional development strategy is through increasing community participation.